Does Paid Family Leave Save Infant Lives? Evidence from United States - Feng Chen (Global Labor Organization (GLO), 2021)
One goal of the paid family leave (PFL) is to help working mothers balance their careers and family responsibilities and hence improve the well-being of their infants. However, most studies of PFL on early childhood outcomes have been based on the analyses of surviving infants. If PFL reduces infant deaths, such analyses would understate the effects. Using the linked birth and infant death data in the U.S. with a difference-in-differences framework, I find that the implementation of a six-week PFL in California reduced the post-neonatal mortality rate by 0.135, or it saved approximately 339 infant lives. The effects were driven by death from internal causes, and there were larger effects for infants with married mothers and infant boys. Additional robustness checks and placebo examinations indicate that the effect is not due to confounding factors or contemporary shocks but causal.
Keywords: J13; J16; J18; 330; paid family leave; infant mortality; child development